Interactionism for the discerning mind? - Shiller, Derek (Philosophical Studies, 2020)
Jaegwon Kim has developed an argument that interactionist dualists cannot account for the causal relations between minds and brains. This paper develops a closely related argument that focuses instead on the causal relations between minds and neurons. While there are several promising responses to Kim's argument, their plausibility relies on a relatively simple understanding of mind–brain relations. Once we shift our focus to neurons, these responses lose their appeal. The problem is that even if mind–brain causal pairing can be explained at no great theoretical cost, the complex interactions non-physical minds would need to have with neurons cannot.